2003
DOI: 10.1177/0115426503018006524
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Fish Oil on Appetite and Other Symptoms in Patients with Advanced Cancer and Anorexia/Cachexia: A Double‐Blind, Placebo‐Controlled Study

Abstract: Background: To determine whether high doses of fish oil, administered over 2 weeks, improve symptoms in patients with advanced cancer and decreased weight and appetite. Methods: Sixty patients were randomly assigned to fish oil capsules or placebo. Appetite, tiredness, nausea, well‐being, caloric intake, nutritional status, and function were prospectively assessed at days 1 and 14. Results: The baseline weight loss was 16 ± 11 and 16 ± 8kginthe fish oil (n = 30) and placebo (n = 30) group, respectively, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
108
1
8

Year Published

2004
2004
2011
2011

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(122 citation statements)
references
References 0 publications
5
108
1
8
Order By: Relevance
“…9 Their study had critical differences in design compared with the current study. First, Bruera et al administered a daily dose of 3 g EPA plus DHA, compared with Ͼ 7 g per day (for a 70 kg patient) in the current study.…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…9 Their study had critical differences in design compared with the current study. First, Bruera et al administered a daily dose of 3 g EPA plus DHA, compared with Ͼ 7 g per day (for a 70 kg patient) in the current study.…”
Section: Discussionmentioning
confidence: 89%
“…Bruera and colleagues reported on a doubleblind controlled study of 60 patients with cancer cachexia, 50% of whom received gelatin fish oil capsules. 9 Those authors found no effect on weight, appetite, or fatigue compared with placebo during the 2 weeks that patients took the capsules. In that study, it was determined that the ingestion of 3 g eicosapentaenoic acid (EPA) plus docosahexaenoic acid (DHA) for a brief period (14 days) had no effect on the cachectic symptoms or markers associated with terminal malignancy.…”
mentioning
confidence: 98%
“…Dietary fish oil in advanced cancer VC Pratt et al EPA, it is perhaps not surprising that the main study (Bruera et al, 2002) did not detect a significant treatment effect on weight or body composition. However, in this smaller subgroup of patients, the magnitude of the change in plasma PL EPA, was significantly related to the amount of weight gained by the subjects receiving fish oil, providing evidence for a dose response relationship.…”
Section: Discussionmentioning
confidence: 94%
“…The patients with advanced cancer were a cohort of subjects participating in a larger study (Bruera et al, 2002). A random sub-sample of 14 subjects per treatment arm were assigned to receive more detailed measures of fatty acid status described here.…”
Section: Subjectsmentioning
confidence: 99%
“…The vast majority of the clinical trials in which fish oil derived n-3 PUFAs were tested report an increase (Wigmore et al, 1996(Wigmore et al, , 2000Barber et al, 1999Barber et al, , 2001Jatoi et al, 2004) or maintenance (Burns et al, 1999(Burns et al, , 2004Fearon et al, 2003) of body weight (BW), whereas in two other clinical trials no effect on the loss of BW was found (Gogos et al, 1998;Bruera et al, 2003). In the latter, however, the supplementation period was only 2 weeks (Bruera et al, 2003) and/or only a small number of patients was included (Gogos et al, 1998). In a clinical trial in pancreatic cancer patients, in which a fish oil-enriched product was tested against an isocaloric/isonitrogenous placebo, no differences between groups were found on either LBM or physical activity.…”
mentioning
confidence: 99%